2018
DOI: 10.17576/jsm-2018-4710-12
|View full text |Cite
|
Sign up to set email alerts
|

Piper sarmentosum as an Antioxidant: A Systematic Review

Abstract: Piper sarmentosum (PS) is an herb with various medicinal properties. The antioxidant activity of PS contributes to many of its pharmacological effects such as anti-hypertension, anti-cancer and anti-diabetes. This systematic review provides information regarding the antioxidant activity of PS. The review was conducted systematically to identify relevant published articles on the antioxidant activity of PS. The collected data was based on the searched articles through PubMed, Science Direct and Scopus databases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…The most abundant compound, hydrocinnamic acid, is a derivative of cinnamic acid, a compound that exhibits strong antioxidant activity due to the presence of a CH=CH–COOH (prop-2-enoic acid) moiety 35 38 . Antioxidant activities of P. sarmentosum extracts identified through DPPH assays have also been reported in other studies 39 , 40 . The DPPH radical model was also applied in our study to evaluate the free radical scavenging activity of P. sarmentosum aqueous extract.…”
Section: Discussionsupporting
confidence: 80%
“…The most abundant compound, hydrocinnamic acid, is a derivative of cinnamic acid, a compound that exhibits strong antioxidant activity due to the presence of a CH=CH–COOH (prop-2-enoic acid) moiety 35 38 . Antioxidant activities of P. sarmentosum extracts identified through DPPH assays have also been reported in other studies 39 , 40 . The DPPH radical model was also applied in our study to evaluate the free radical scavenging activity of P. sarmentosum aqueous extract.…”
Section: Discussionsupporting
confidence: 80%
“…In Malaysia and Indonesia, this plant is used in traditional medicine for treating toothache, pleuritis, asthma, diabetes, hypertension, joint pain and fungal infections. Phytochemicals of Ps indicate that the methanol extracts of this plant contain naringenin, a flavonoid [ 23 , 29 , 54 ]. Flavonoids are known to reduce bone loss and increase bone strength in ovariectomised rats [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is known locally in Malaysia as ‘daun kaduk’. Phytochemical studies of Piper species led to the separation of several clusters of active components, such as amides, propenylphenols, lignans, steroids, flavonoids, ketones, carboxylic acids, phytosterols and phenyls [ 21 , 22 , 23 ]. Many studies have shown that Piper sarmentosum possesses pharmacological effects such as anti-tuberculosis [ 19 , 24 ], anti-cancer [ 25 ], hypoglycaemic action [ 26 , 27 ], anti-malarial [ 28 ], antioxidant [ 29 ], neuromuscular blocking action [ 30 ], anti-atherosclerosis [ 31 ] and anti-inflammation [ 32 ] activities.…”
Section: Introductionmentioning
confidence: 99%
“…A significant increase in SOD levels showed that mangosteen extract or products promote the activity of SOD enzyme in neutralizing oxidative stress. A significant decrease in the SOD level could be due to the direct activity of mangosteen extract or products in neutralizing ROS which reduces the need for an antioxidant enzyme such as SOD (Ismail et al, 2018). All studies with evaluated CAT (n = 13) and GPx (n = 10) levels showed a significant increase in both enzyme levels after the subjects were treated with mangosteen extract or product.…”
Section: Continuedmentioning
confidence: 99%